Parent–subsidiary geographic dispersion and debt aggressiveness: Analysis from the tax enforcement perspective - Liu, Xiaomei; Yang, Zhenhe; Wang, Yuanqing; Gao, Boyuan (International review of economics & finance, 2024)
Prior studies of corporate debt policy primarily focused on the overall company and ignored the impact of geographical dispersion between the parent and subsidiary companies. Using listed companies in China from 2007 to 2017 as the sample, this study explores the influence of the spatial geographic dispersion of parent and subsidiary companies on the radicalism of corporate debt policy based on a series of relevant models. Moreover, it discusses the regulatory effect of tax collection and management on the aforementioned relationship. The findings suggest a significant and positive relationship between the geographic dispersion of parent–subsidiary relationships and the aggressiveness level of corporate debt policy. Furthermore, tax enforcement has a significant moderating effect on this relationship. Results of this study enrich the research content of the factors affecting corporate debt policy and serve as an important reference for listed companies implementing regional diversification strategies. This study further provides inspiration for the government to improve tax collection and management work and optimize the financing platform.